Barriers to financial product innovation in Islamic banks in Pakistan: An interpretive structural modeling approach. Issue 2 (2nd January 2020) - Chaudhry, Naveed Iqbal; Roomi, Muhammad Azam; Dar, Sidra
Abstract : Purpose: The purpose of this paper is to identify barriers to financial product innovation in the Islamic banks (IBs) of Pakistan. This paper also aims to establish the relationship among the barriers and present them in a hierarchical model after classification. Design/methodology/approach: This study is exploratory and qualitative in nature. A total of ten experts from the IBs and from academia have been interviewed to collect data. Literature has also been reviewed to identify the barriers. Interpretive structural modeling (ISM) analysis has been used to establish relationship among the barriers, to rank and to come up with a hierarchical model of barriers. Findings: This research paper makes out, ranks and classifies the nine most important barriers to product innovation in the IBs in Pakistan, including high innovation cost; lack of customer awareness; difference of school of thoughts between members of Shari'ah board; non-compatibility between product design department and members of Shari'ah board; lack of research and development; non-acceptability of concept of Islamic banking; lack of training regarding a new product; imitation of a new product by competitors; and the limited use of new product development tools. Originality/value: This study offers originality in its nature of being qualitative and the use of ISM technique. It is also the first research project regarding identification of barriers in the IBs in Pakistan.